The Pan-Cytokeratin Staining Intensity and Fractal Computational Analysis of Breast Tumor Malignant Growth Patterns Prognosticate the Occurrence of Distant Metastasis - Rajković, Nemanja; Li, Xingyu; Plataniotis, Konstantinos N.; Kanjer, Ksenija; Radulovic, Marko; Milošević, Nebojša T. (Frontiers in Oncology, 2018)
Improved prognosis of breast cancer outcome could prolong patient survival by reliable identification of patients at high risk of metastasis occurrence to benefit from more aggressive treatments. Based on such clinical need, we prognostically evaluated the malignant cells in breast tumors as the obvious potential source of unexploited prognostic information. The patient group was homogeneous, without any systemic treatments or lymph node spread, with smaller tumor size (pT1/2) and a long follow-up. Epithelial cells were labeled with AE1/AE3 pan-cytokeratin antibody cocktail and comprehensively analyzed. Monofractal and multifractal analysis was applied for quantification of distribution, shape and texture of malignant cell clusters, while mean pixel intensity and total area were measures of the pan-cytokeratin immunostaining intensity. The results surprisingly indicate that simple binary images and monofractal analysis provided better prognostic information then greyscale images and multifractal analysis. The key findings were that shapes and distribution of malignant cell clusters (by binary fractal dimension; AUC=0.29), their contour shapes (by outline fractal dimension; AUC=0.31) and intensity of the pan-cytokeratin immunostaining (by mean pixel intensity; AUC=0.30) offered significant performance in metastasis risk prognostication. These results reveal a surprising association of the lower pan-cytokeratin staining intensity with the high metastasis risk. Another interesting result was that multivariate analysis could confirm the prognostic independence only for fractal and not for intensity features. The obtained results reveal several novel and unexpected findings highlighting the independent prognostic efficacy of malignant cell cluster distribution and contour shapes in breast tumors.